A New Option for the Reconstruction of Orbital Floor Defects: The Olecranon Bone Graft. Issue 4 (October 2015) - Yeşiloğlu, Nebil; Şirinoğlu, Hakan; Sarici, Murat; Temiz, Gökhan; Filinte, Gaye Taylan
Abstract : Background: Orbital floor fractures are one of the most commonly encountered maxillofacial fractures due to its weak anatomic structure. Autogenous bone is a commonly used option for the reconstruction of orbital floor defects by many authors and institutions. This article introduces the olecranon bone graft as a new option for orbital floor reconstruction. Methods: The study is based on the analysis of 13 patients with orbital floor fracture operated on by using the olecranon bone graft. The mean age of the patients was 34 years 6 months. The physical examination of 5 (38.5%) patients revealed diplopia, 3 (23%) patients gaze restriction, 3 (23%) patients infraorbital nerve paresthesia, and 7 (53.8%) patients enophthalmos with various degrees. The mean defect size was 21.15 × 14.08 mm and the mean defect field was 2.98 cm 2 . All patients were operated on under general anesthesia and the orbital floor defect was exposed subperiosteally. The olecranon bone graft was harvested in 10 cases using a 3-cm incision over the olecranon and in 3 cases using the bone biopsy trephine and placed to the orbital floor defect after shaping with cottle cartilage crusher. Both clinical and radiological follow-up examinations were carried out in the postoperative period. Results: The mean follow-up period of the patients was 7.92 months. The mean size of the grafts was 24.85 × 17.54 mL. The mean field of the grafts was 4.26 cm 2 . Among the 7 patients who had enophthalmos before the surgery, complete resolution was observed in 6 (85.7%) patients and in the remaining 1 (14.3%) patient, the degree of enophthalmos was found to be significantly reduced at the postoperative sixth month examination. All patients with preoperative diplopia and gaze restriction showed complete healing in the postoperative period. Eleven (84.6%) patients showed mild pain at the olecranon donor area with complete relief in the postoperative 3 days and the remaining 2 (15.4%) patients had moderate pain sensation which completely passed away at the postoperative fifth day. Conclusions: The olecranon bone graft is a suitable autogenous option for orbital floor reconstruction due to its considerable strength and molding capacity with low rates of complications and donor area morbidity.